The Influence of Scent Marketing on Consumers' Approach and Avoidance Behaviour in the High-End Fashion Industry - van Niekerk, Chantel; Goldberg, RH (Mediterranean Journal of Social Sciences, 2021)
Existing literature falls short in that it fails to directly recognise the potential that lies within scent marketing and its influence on consumers’ behaviour, especially in high-end fashion stores. The study aimed to explore the influence of scent marketing on consumers’ approach and avoidance behaviour in the high-end fashion industry. The study was qualitative in nature and followed an exploratory research design. A non-probability snowball sampling method was used to recruit participants. Data was collected by means of three focus group sessions. The collected data was analysed by using the Morse and Field approach, and by making use of ATLAS.ti qualitative data analysis software. SPSS software was also used to analyse the demographic results. The results indicate that consumers’ response stimuli often depend on emotional stimuli they experience, which will lead to an approach or avoidance response. Scent marketing can boost approach behaviour, if implemented correctly. Based on the results, it is recommended that retail stores, more specifically high-end fashion stores, should make use of scent marketing to attract consumers to the store, keep them browsing for longer periods, enhance purchases and make them feel comfortable. Scent can have a positive influence on consumer’s evaluations, reactions and the intention to visit and revisit a store. This can result in consumers spending more time and money in the store. Furthermore, if scent marketing is implemented correctly, it could also boost brand identity and create a competitive advantage for that specific store.   Received: 27 February 2021 / Accepted: 15 June 2021 / Published: 8 July 2021